Bimbingan Pijat Jantung dalam Upaya Meningkatkan Pengetahuan dan Keterampilan tentang Resusitasi Jantung Paru pada Orang Awam di Balikpapan - Lusiani, Etik; W, Sisilia Indriasari; Saputra, Agung Kurniawan (Jurnal Abdimas Kesehatan (JAK), 2024)
Emergency incidents can occur anywhere, this condition requires community participation to help victims before they are found by health workers, which is very important. Cardiopulmonary resuscitation health education for the lay public is the main thing to increase the ability to help life-threatening victims before going to the hospital. Health information about cardiopulmonary resuscitation (CPR) for people aims to increase knowledge and be able to help victims of cardiac arrest. The activities are carried out in 2 methods offline and online which are packaged in the form of questions, answers and direct practice. The number of participants was 30, health education material was delivered and questions and answers were held for ± 30 minutes about RJP, followed by CPR practice for ± 20 minutes. The tools used are small manikins and pillows and there are group divisions and each group is accompanied by a guide. The results before health education and CPR practice were carried out, the level of knowledge of respondents was good, 15 people (50%), 5 people (17%) had sufficient knowledge and 10 people (33%) had less knowledge. After being given health education there was a change in the knowledge category, namely 18 people (60%) had good knowledge, 7 people (23%) had sufficient knowledge and 5 people had less knowledge (17%) about heart attacks and CPR skills. This community service hopes that ordinary people can carry out Cardiopulmonary Resuscitation as basic life support (Basic Cardiac Life Support) and management of cardiac arrest victims outside the hospital